Լիբանանահայ երաժշտահան Պօղոս Ճելալեանի մանկավարժական մեթոտի առանձնահատկությունները - Աւեսեան, Կարօ (տպ. Atlas)
Over the course of his career as a composer, the Lebanese-Armenian Boghos Gelalian (1927—2011) made a remarkable contribution to the preservation of Armenian cultural heritage in the Diaspora as well as to the development of the Lebanese performing school of art and music. In addition, he prepared a significant number of piano performers and an educated circle of music lovers in Lebanese cultural society. Gelalian was a devoted instructor and a skilled pedagogue, who revealed his students’ musical abilities and developed their skills by informative and educational methods with painstaking care and unremitting attention.
Keywords: Արուեստ